Determinants of perceived university performance among public-sector universities of Pakistan - Khan, Quaisar Ijaz (2019)
Universities are the symbol of prestige for nations. The performance of the universities depends upon on the faculty members’ qualification and their potential contribution towards knowledge. Human resource management practices are designed to enhance individuals’ performance; who have different inbuilt personality traits, to achieve organizational goals with organizational justice. Whereas, the employees in any organization are termed as the dynamic asset for contributing towards institutional performance. Therefore, career success of the faculty members was taken in this study as mediating variable. For hauling the research study, academicians were chosen from Pakistan’s public-sector universities. Whereas, to support the conceptual framework, the researcher has applied the Theory of Dynamic Capabilities as the underpinning theory. For sampling purposes, proportionate stratified sampling was adapted; random sampling was used to select the academics within each stratum. The questionnaire was distributed among individuals personally; response rate remained 59 percent. Afterword, data were cleaned for missing values, outliers, aberrant values and tested for normality, reliability and validity. Hypotheses were tested by applying partial least squares - structural equation modelling technique through statistical software SMART PLS registered version 3.2.6. The researcher found statistically significant relationships between (i) personality traits and perceived university performance, (ii) HRM practices with perceived university performance, (iii) organizational justice with perceived university performance, (iv) career success with perceived university performance, (v) personality traits with career success, (vi) HRM practices with career success and (vii) organizational justice with career success. However, the partial mediation of career success was observed between (viii) personality traits and perceived university performance, (ix) HRM practices and perceived university performance, (x) organizational justice and perceived university performance. The construct in the context of Pakistan in amongst the preliminary studies. The findings will be helpful for higher education commission of Pakistan for designing strategies.